Genetic correlates of clarithromycin susceptibility among isolates of the Mycobacterium abscessus group and the potential clinical applicability of a PCR-based analysis of erm(41) - de Carvalho, Natalia F.G.; Pavan, Fernando [UNESP]; Sato, Daisy N. [UNESP]; Leite, Clarice Q.F. [UNESP]; Arbeit, Robert D.; Chimara, Erica (Oxford University Press (OUP), 2018)
Objectives: To define the genetic basis of clarithromycin resistance among isolates of the Mycobacterium abscessus group (MAG). Methods: We analysed 133 isolates identified as MAG. Species identification was confirmed by sequencing the rpoB gene. Clarithromycin susceptibility testing was performed according to CLSI recommendations, with an extended 14 day incubation. Known resistance genotypes of erm(41) and rrl were identified by sequencing; the presence of deletions in erm(41) was detected by PCR. Results: The 133MAG isolates included 82M. abscessus, 27Mycobacteriummassiliense and 24 Mycobacteriumbolletii. After the 3 day incubation, only five isolates demonstrated clarithromycin resistance (R); after 14days of extended incubation, an additional 92 exhibited inducible resistance (IR), with the remaining being susceptible (S). The distribution of susceptibility phenotypes varied among the species. Among M. abscessus isolates, 11% were S, 84%IR and 5%R; among M. bolletii isolates, 96%were IR and 4%R; and among M. massiliense isolates 100%were S. Sequencing of rrl identified only a single isolate with the A2058G mutation. Deletions in erm(41) were present in 30 susceptible isolates; among the remaining 103 isolates, 97 were R or IR (sensitivity, 83%; specificity, 100%; positive predictive value, 100%; negative predictive value, 94%). Among the six susceptible isolates without deletions, all carried the erm(41) T28C pointmutation. Conclusions: A significant proportion of MAG isolates demonstrate inducible resistance to clarithromycin that is only detectable with an extended 14 day incubation. Further, the majority of clarithromycin-susceptible MAG isolates have characteristic deletions in erm(41) that can rapidly and reliably be detected by a simple PCR.